The role of the family environment and parental nutritional knowledge in the prevention of behavioral feeding disorders in toddlers and preschool children – a narrative review - Paulina Kawecka; Małgorzata Kostecka (Journal of Health Inequalities)
Pediatric feeding disorders are generally observed between the ages of 1 and 3 years, but they can have long-lasting consequences that affect various areas of life. Social and environmental factors, including dietary patterns and strategies introduced by parents, and emotions that accompany eating play a key role. The aim of this study was to review the literature on the possible causes of the development of feeding disorders in children, and to highlight the influence of the family environment, including the eating habits of the parents, on the prevention, onset and therapy of feeding disorders. Parents should assist their children in developing healthy dietary patterns, becoming familiar with new foods, and learning through observation and association. Pressure to eat usually has the opposite effect, and it further reduces a child’s food intake. Offering rewards for eating or bargaining with picky eaters may deliver benefits, but only if the child is willing to try a novel product on the spot. Parental views on child feeding and their willingness to implement experiential learning strategies (through sensory play and games) also play an important role in shaping desirable feeding behaviors and increasing the child’s intake of fruits and vegetables. Children learn through observation, and parents should participate in meal preparation, preferably from the beginning to the end of the process. Sensory-based food education also generates positive outcomes by increasing children’s intake of fruits and vegetables, and this approach should be used to prevent selective eating. According to experts, parents can use various strategies to familiarize children with food. From the dietary perspective, repeated exposure to a given product is most likely to result in early food acceptance. The promotion of healthy eating habits in early childhood can also provide numerous benefits for children’s health and wellbeing in the future.